FENOMENA TA’ARUF ONLINE DAN PRAKTIK KOMODIFIKASI PERKAWINAN DI DUNIA DIGITAL - Fathor Rahman; Ghazian Luthfi Zulhaqqi (Kafa`ah: Journal of Gender Studies, 2020)
This paper explains a phenomenon of ta’aruf which has been flourishing in the digital world. With the mode of revitalization of pure Islamic teachings and overlaid with the doctrine of hijrah, ta’aruf onlne is a way to invite man and woman to marry without dating. However, this article also explains the other side relating to this phenomenon of ta’aruf which in the process is involved in the practice of commodification. In this connection, there are two focus of studies reviewed in this paper, first, what is the background of the emergence of the phenomenon of online ta’aruf. Second, how the online ta’aruf phenomenon is commodified by its users. Using qualitative methods, research explores various website s and accounts that provide online ta’aruf services. The findings are that online ta’aruf in the digital world has been motivated by the movement of migratory trends in the Muslim community in recent years. However, in its development, online ta’aruf was later commodified by the perpetrators because there were interested people and the market wanted it.